Stabilization of the radial clear in the pumping assembly of the supply pump improvement by improving the structure of the slide bearing bushing (Modern Problems of Metallurgy, 2022)
The performance of axial-piston hydraulic feed pumps depends on the technical condition of the coupling parts that form a radial gap in the pumping unit of the pump. The dynamics of its growth is largely due to the technical condition of parts that form a radial gap in the plain bearings of the pumping pump assembly: «drive shaft pin - bushing hole», «driven axle pin - bushing hole». Stabilization of a radial backlash in sliding bearings is possible by carrying out constructive improvement of the plug which will provide reduction of a contact angle of surfaces of friction of details in couplings. The aim of the work is to ensure the stabilization of the radial clearance in the pumping unit of the feed pump by developing constructive measures to reduce wear of parts in its plain bearings. From the analysis of the operating conditions of the plain bearing it is established that the reduction of the friction force is possible due to the reduction of the contour pressures and the increase of the area of liquid friction between the surfaces of the parts. Providing such conditions is possible by using combined bushings, which consist of working and guide bushings, between which is installed an elastic damping element in the spherical channels of which are additional compensation springs, which are placed in a circle through . The reduction of the friction force when using a combined sleeve with compensating springs is explained by the formation of the deformation component of the friction force at the vertices of the microroughness of the sleeve surface, as the spring elasticity is 4% less than the modulus of elasticity of the sleeve material. The lower value of the moment of friction forces at the end of the test is due to the constant absorption of vibration loads by the elastic damping element, the elasticity of which is 2% less than the modulus of elasticity of the sleeve material, which also reduces the contact area. The total less wear of the experimental friction pair is due to the reduction of the contact area of the shaft with the sleeve in the area of maximum values of friction forces.